RAGAM BAHASA PEDAGANG SAYUR DI PASAR KIDUL DUSUN BLOKAGUNG DALAM RANAH FONOLOGI - Yulia Dwi Oktafiani (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this study is to be able to describe the results of the utterances of vegetable traders in the kidol market of Blokagung sub-village in the phonological domain and also be able to find out the factors that cause the various languages of the traders. The method used is descriptive qualitative. The method does not require a count of numbers and is used to describe or write down events at the time the research was conducted. Data and data sources needed in this study are in the form of words, phrases, sentences in the utterances of vegetable traders in the kidul market of Blokagung hamlet. The results of the study describe the various languages of the vegetable traders' utterances in terms of phonological studies. There are phoneme changes (so buyers can hear clearly the types of vegetables offered), phoneme removal (to speed up traders delivering speech when offering their vegetables), phonemes additions (for fluent traders in speaking) and phonemes reduction (for fluent traders in speaking). So that the purpose of traders offering vegetables can be done well and accepted by the buyer. From this research, there are three factors that cause a variety of languages, namely the habit factor, attracting the attention of the seller, and the factor of quickly selling.